APPLICATION OF THE TEAM GAMES TOURNAMENT METHOD TO IMPROVE MASTERY OF ARABIC VOCABULARY AT SMP IT AL-MUNADI MEDAN - Nasution, Dea Safhira; Salamuddin, Salamuddin (Abjadia : International Journal of Education, 2024)
This study is a Classroom Action Research (CAR) aimed at increasing enthusiasm for learning and revealing the effectiveness of the Team Games Tournament (TGT) method in enhancing students' mastery of Arabic vocabulary. The subjects were 29 students of class VII at SMP IT Al-Munadi. Data collection techniques included observation, interviews, and documentation. The research was conducted in two cycles, following the stages of (1) planning, (2) implementing, (3) observing, and (4) reflecting. Children naturally enjoy listening and playing, making play an important part of the teaching and learning process for young students. Vocabulary mastery among students before using the TGT method was categorized as excellent (78-88), good (67-77), and less good (below 67). After using the TGT method, vocabulary mastery improved, with criteria of excellent (90-100), good (78-88), and poor (50-60). The results indicate that students at SMP IT Al-Munadi enjoy learning Arabic through play and can more easily remember the vocabulary taught. Some students were able to memorize vocabulary after multiple repetitions by the teacher. In conclusion, playing techniques can effectively enhance students' mastery of Arabic vocabulary, particularly at SMP IT Al-Munadi.